Antithrombotic and Hemorrhagic Effects of DX-9065a, a Direct and Selective Factor Xa Inhibitor: Comparison with a Direct Thrombin Inhibitor and Antithrombin Ill-Dependent Anticoagulants - Morishima, Yoshiyuki; Tanabe, Kiyoshi; Terada, Yasuko; Hara, Tsuyoshi; Kunitada, Satoshi (Thrombosis and Haemostasis, 1997)
(+)-2S-2-[4-[[(3S)-l-acetimidoyl-3- pyrrolidinyl]oxy]phenyl]-3-[7-amidino-2-naphthyl]propanoic acid hydrochloride pentahydrate (DX- 9065a) is an antithrombin III (AT III)-independent and selective inhibitor of activated blood coagulation factor X (FXa). The aim of the present study was to compare the antithrombotic and hemorrhagic effects of DX-9065a with a direct thrombin inhibitor and AT Ill-dependent anticoagulants in rat models of thrombosis and bleeding.Rats were administered intravenously DX-9065a (0.1-1 mg/kg/h), argatroban (0.1-1 mg/k/h), low molecular weight heparin (25-100 anti- XaU/kg/h), unfractionated heparin (25-100 anti-XaU/kg/h) or Orgaran (30-300 anti-XaU/kg/h) for 1 h. DX-9065a dose-dependently inhibited both thrombus formation and elevation in plasma thrombin-AT III complex (TAT) level in a copper wire-inserted arteriovenous (AV) shunt model in rats. The dose required for 50% inhibition of thrombus formation was 0.27 mg/kg/h. DX-9065a did not prolong transection bleeding time up to 7.78 mg/kg/h. Argatroban and AT Ill-dependent anticoagulants also inhibited both thrombus formation and TAT elevation, but prolonged bleeding time at a slightly higher dose than the effective dose. These results suggest that direct and selective inhibition of factor Xa by DX-9065a is preferable for the treatment of thrombosis in the aspect of lack of compromising primary hemostasis.